Sequence-specific labeling of superhelical DNA by triple helix formation and psoralen crosslinking - Pfannschmidt, Claudia; Schaper, Achim; Heim, Gudrun; Jovin, Thomas M.; Langowski, Jörg (Nucleic acids research, 1996)
Site-specific labeling of covalently closed circular DNA was achieved by using triple helix-forming oligonucleotides 10, 11 and 27 nt in length. The sequences consisted exclusively of pyrimidines (C and T) with a reactive psoralen at the 5′-end and a biotin at the 3′-end. The probes were directed to different target sites on the plasmids pUC18 (2686 bp), pUC18/4A (2799 bp) and pUC18/4A-H1 (2530 bp). After triple helix formation at acid pH the oligonucleotides were photo-crosslinked to the target DNAs via the psoralen moiety, endowing the covalent adduct with unconditional stability, e.g. under conditions unfavorable for preservation of the triplex, such as neutral pH. Complex formation was monitored after polyacrylamide gel electrophoresis by streptavidin-alkaline phosphatase (SAP)-induced chemiluminescence. The yield of triple helix increased with the molar ratio of oligonucleotide to target and the length of the probe sequence (27mer > 11mer). The covalent adduct DNA were visualized by scanning force microscopy (SFM) using avidin or streptavidin as protein tags for the biotin group on the oligonucleotide probes. We discuss the versatility of triple helix DNA complexes for studying the conformation of superhelical DNA.